Antiulcer mechanisms of Vernonia condensata Baker: A medicinal plant used in the treatment of gastritis and gastric ulcer. (26th May 2016) - Boeing, Thaise; da Silva, Luisa Mota; Somensi, Lincon Bordignon; Cury, Benhur Judah; Michels Costa, Ana Paula; Petreanu, Marcel; Niero, Rivaldo; de Andrade, Sérgio Faloni
Abstract: Ethnopharmacological relevance: The leaves from Vernonia condensata Baker are broadly used in folk medicine for the treatment of gastric ulcers and dyspepsia. The Brazilian Public Health System (SUS) describes this species as having the potential to serve as a new herbal product with therapeutic benefits. Aim of the study: The purpose of the study was to evaluate the gastroprotective activity and gastric healing properties of a crude ethanolic extract from leaves of V. condensata (CEEV) in different animal models. Materials and methods: In order to assess the gastroprotective potential of CEEV, ulcer models were established using ethanol and indomethacin. The gastric healing effect was then evaluated in the acetic acid-induced ulcer model, where the tissue was used to assess oxidative levels (reduced glutathione and lipid hydroperoxide levels, as well as superoxide dismutase and catalase activity), inflammatory [myeloperoxidase (MPO)] parameters, and mucin content. Furthermore, the ligature pylorus model, with and without secretagogue stimuli, was employed to investigate the mechanism of action of CEEV. In addition, H + K + -ATPase activity, MPO activity, and antioxidant activity through the DPPH assay were examined through in vitro trials. Phytochemical analyses were also performed. The ethanol/HCl-induced gastric ulcer method was employed to verify the gastroprotective effect of the main compound in CEEV. Results: CEEV (30 and 300 mg/kg, p.o) exhibited gastroprotective activity and prevented both gastric lesions induced by ethanol or indomethacin in rats. The gastric healing effect of CEEV (300 mg/kg, p.o. taken twice a day for a duration of seven days) was confirmed by examining the macroscopic and microscopic appearance of chronic gastric ulcers induced by acetic acid in rats. The restorative effect of CEEV was accompanied by a significant increase in mucin content (PAS staining) and by a reduction in oxidative stress and inflammatory parameters at the site of the ulcer. Moreover, CEEV (300 mg/kg), administered via an intraduodenal route, significantly reduced the volume, pH, total acidity and pepsin activity of gastric content in the pylorus ligature model in rats. The gastric acid antisecretory effect of CEEV was maintained even in the presence of cholinergic and gastrinergic, but not histaminergic, stimuli. In vitro, CEEV (1–10 µg/ml) was able to scavenge free radical DPPH, but did not promote inhibitory effects on MPO or H +, K + -ATPAse activity. Phytochemical analysis of CEEV indicated that luteolin is the main compound present in the extract. However, luteolin (1, 3 and 10 mg/kg, p.o or 1 mg/kg, i.p.) did not promote gastroprotection against ethanol/HCl in mice. It is also important to mention that oral administration of CEEV did not produce any sign of acute toxicity in animals. Conclusions: V. condensata extract demonstrates gastroprotective effects through the inhibition of gastric secretion via cholinergic and gastrinergic pathways. Furthermore, it exhibits cytoprotective effects, involving antioxidant activity, an increase in mucin content and inhibition of neutrophil migration. Thus, this medicinal plant may be a suitable natural source for the prevention and treatment of gastric lesions. Graphical abstract: